Construction of M. Umer Chapra's Economic Thoughts in Realizing Efficiency and Justice - Khusniati Rofiah; Mohammad Ghozali (Universitas Darusssalam Gontor, 2020)
A study of thought in the economic setting of Muslims. This study aims to find out the concept of thinking of a Muslim economist, M. Umer Chapra examines the existence of universal economic problems faced by the nations of the world, namely the lack of human well-being due to lack of efficiency and justice in the allocation of God-given resources, which cannot be solved by the conventional system. As an alternative to achieving efficiency and justice, Chapra proposes an Islamic economic system that has a worldview and strategy in line with the Islamic sharia that enables it to print a fair and viable solution in Muslim countries. For Chapra, the main purpose of the management of allocation and distribution should not deviate from the maqashid al-sharia (sharia goal) which is the well-being of the people. Method of this study using literacy, data collection and collection of objects, In this study it is found that the world view of Islamic economy according to Chapra is based on three basic principles: monotheism, caliphate and 'is. Harmony between the al-sharia and the worldview is not enough to bring efficiency and justice to the well-being of the people, according to Chapra needed a strategy for organizing the economic system with four necessary and mutually supportive elements: filter mechanism, correct motivation, socio-economic and financial restructuring, and the role of the nation.